2015
DOI: 10.1016/j.yebeh.2015.03.032
|View full text |Cite
|
Sign up to set email alerts
|

Implicit and explicit self-esteem discrepancies in people with psychogenic nonepileptic seizures

Abstract: Purpose: Self-esteem (SE), or one's sense of competence and worth, is reduced in many mental and physical\ud disorders. Low SE is associated with perceived stigma and disability and poor treatment outcomes. The present\ud study examined implicit and explicit SE (automatic and deliberate views about the self) in people with epilepsy\ud and people with psychogenic nonepileptic seizures (PNESs). Discrepancies between implicit SE and explicit SE\ud have been found to correlate with psychological distress in disord… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 55 publications
(75 reference statements)
1
9
0
Order By: Relevance
“…Dimaro et al found discrepancies between explicit and implicit anxiety and self-esteem measures in the PNES but not the other two participant groups. They interpreted their findings as indicating that PNES may serve a protective function: whilst patients with PNES (explicitly) self-reported high levels of anxiety and low levels self-esteem, the Implicit Relational Assessment Procedure (IRAP) measures suggested that their self-image was not characterised by elevated anxiety or reduced self-esteem [25,41].…”
Section: Discussionmentioning
confidence: 99%
“…Dimaro et al found discrepancies between explicit and implicit anxiety and self-esteem measures in the PNES but not the other two participant groups. They interpreted their findings as indicating that PNES may serve a protective function: whilst patients with PNES (explicitly) self-reported high levels of anxiety and low levels self-esteem, the Implicit Relational Assessment Procedure (IRAP) measures suggested that their self-image was not characterised by elevated anxiety or reduced self-esteem [25,41].…”
Section: Discussionmentioning
confidence: 99%
“…A wealth of studies has provided insights into the psychosocial features of PNES (8,41), but the biological underpinnings of the disorder have received much less attention and are still poorly understood. However, an emerging and growing body of evidence has finally started to unravel the neurobiological basis of PNES (42)(43)(44).…”
Section: Neurobiology Of Pnesmentioning
confidence: 99%
“…For a long time, PNES have been considered disorders generated in the absence of biological and organic substrates. Thus, most of the attention has been focused on the psychosocial correlates of the condition (8,9) and PNES patients have been mainly investigated and treated with psychoanalytic/psychodynamic approaches. The psychosocial origins of PNES have been largely endorsed by specialists as well as patients who often find it difficult to reconcile themselves with the idea of suffering from a disorder that lacks an organic basis (10,11).…”
Section: Introductionmentioning
confidence: 99%
“…In some circumstances, focusing on the physical aspects of one's experiences may constitute a highly adaptive response that enables the individual to retain a relatively normal sense of self and well-being in the face of on-going adversity (Dimaro et al, 2014(Dimaro et al, , 2015. Indeed, there is evidence that patients who do not experience subjective fear symptoms during their panic attacks are better adjusted than those who do (Chen, Tsuchiya, Kawakami, & Furukawa, 2009).…”
Section: Emotional Processingmentioning
confidence: 99%